PENERAPAN PENDIDIKAN KARAKTER DALAM PROSES PEMBELAJARAN PADA SISWA DI SDK PAUTOLA - Jesika Anastasia Kosto Ngode; Anjelina Bebhe; Maria Natalia Mugi; Yuliana Andini Mau; Maria Desidaria Noge (STKIP Subang, 2025)
The purpose of this study is to describe the implementation of character education in the learning process for elementary school students. This type of research is a qualitative field study conducted at SDK Pautola. Data collection techniques used were observation, interviews, and documentation. The instruments used in this study were structured observation sheets to record student and teacher behavior during the learning process, as well as semi-structured interview guides used to obtain in-depth information from teachers and students regarding the implementation of character education. The data obtained were analyzed using the Miles & Huberman analysis technique, which includes four stages: data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that character education can be implemented effectively through three main ways. First, the integration of character values ​​into the curriculum, namely by incorporating values ​​such as honesty, responsibility, discipline, and cooperation into learning objectives, materials, and assessments in each subject. Second, activity-based learning, where students are actively involved in activities such as group discussions, projects, hands-on practice, and social activities that foster positive attitudes and behaviors, not just academic skills. Third, the development of a supportive school environment, namely creating a conducive school culture through teacher role models, consistent rules, and an atmosphere of safety and mutual respect. This research confirms that teachers and schools have a crucial role as the primary implementers of character education, because the successful formation of student character requires a shared commitment and continuous implementation in all school activities.